The Impact of Training and Compensation on the Performance of Tagrinov Facilitators on Visitors’ Satisfaction - Saptianty, Nila Jania; Hubeis, Aida Vitayala Sjafri; Purwono, Joko (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the direct and indirect influence of training, compensation, and performance of service providers on visitor satisfaction in Tagrnov using the SEM-PLS analysis method, as well as evaluating the level of visitor satisfaction with Tagrinov using the IPA analysis method. The results of SEM-PLS analysis show that implementer performance does not have a significant influence on visitor satisfaction, while compensation and training have a significant influence on visitor satisfaction and implementer performance. However, indirect measurements show that compensation and training do not have a significant effect on visitor satisfaction through the performance of service providers. IPA analysis assesses the level of suitability to determine how satisfied visitors are with the Tagrinov facilitator's performance and how well the facilitator understands visitors' needs. Various attributes are assessed and categorized in four different quadrants based on their level of influence and importance on visitor satisfaction, with improvement recommendations given for certain attributes.